A unique case of eyelid metastasis from chondroid chordoma - Huayan Ren; Xueyan Zhao; Na Wei; Huifen Huang; Wencai Li; Huixiang Li (Wolters Kluwer Medknow Publications, 2019)
A unique case of eyelid metastasis from nasopharyngeal chondroid chordoma in a 63-year-old woman was reported. Chordomas are rare tumors of the bone deriving from remnants of the embryonic notochord. Histologically, the tumor showed lobulated structure and concludes two types of cells: liquid drop cell and small round/cubic cell. Immunohistochemically, AE1/AE3, epithelial membrane antigene (EMA), and S100 showed a uniform and strong positivity. It has a great capacity for recurrence and malignant transformation, despite their slow-growing nature. The most common sites of metastases are liver, lungs, and bones. The eyelid metastasis from chordoma is an extremely rare finding, which may suggest a poor prognosis for the patient. Its significant clinicopathological characteristic could prompt us to take it into consideration when assessing the patient's prognosis.